2017
DOI: 10.1111/echo.13784
|View full text |Cite
|
Sign up to set email alerts
|

Use of linear and convex ultrasound transducers for evaluation of retrosternal area in patients after cardiac surgery

Abstract: The use of linear and convex transducers is usually reserved for ultrasound imaging of vessels, abdominal organs, and lungs. However, the use of these transducers may be extended for the evaluation of thoracic structures. We describe our experience with the use of linear and convex transducers in the evaluation of the retrosternal area, which is usually difficult to visualize by conventional echocardiography and so could provide improved diagnostic information in patients after cardiac surgery. K E Y W O R D S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…28 Besides the increased use of LUS, it was found that the ingenious application of linear and convex transducers for evaluation of retrosternal area could provide additional diagnostic information beyond conventional echocardiography after pediatric cardiac surgery. 29 However, limited data had been found in children undergoing lateral thoracotomy cardiac surgery. To our knowledge, this is the first randomized controlled trial using LUS to investigate the effect of P-RM in children undergoing lateral thoracotomy cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Besides the increased use of LUS, it was found that the ingenious application of linear and convex transducers for evaluation of retrosternal area could provide additional diagnostic information beyond conventional echocardiography after pediatric cardiac surgery. 29 However, limited data had been found in children undergoing lateral thoracotomy cardiac surgery. To our knowledge, this is the first randomized controlled trial using LUS to investigate the effect of P-RM in children undergoing lateral thoracotomy cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The perioperative use of LUS could significantly reduce the frequency of radiographic examinations associated with substantial cost benefits 28 . Besides the increased use of LUS, it was found that the ingenious application of linear and convex transducers for evaluation of retrosternal area could provide additional diagnostic information beyond conventional echocardiography after pediatric cardiac surgery 29 . However, limited data had been found in children undergoing lateral thoracotomy cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this research identifies strategies for designing doubly curved acoustic arrays that achieve focusing capabilities similar to a spherical segment transducer. The flat foldability and developability of this array opens up a new approach to tackle problems of manufacturing, transport, and deployment for such focusing transducers to be used in medical practice (Ji et al, 2008), imaging (Cantinotti et al, 2018; Vilkomerson et al, 1992), and so on. Furthermore, this research can be extended to study numerous curved profiles (Song et al, 2017) such as ellipses, parabolas, and more, which might have unexplored potential applications.…”
Section: Discussionmentioning
confidence: 99%
“…Wave focusing properties of spherically focused transducers are employed in various areas of engineering and medical fields. Numerous applications of these transducers are found in optics (Li et al, 1985), underwater communication (Merkens and Oleson, 2018), structural health monitoring (Koduru and Rose, 2012), ultrasound-based surgery (Ji et al, 2008), medical imaging (Cantinotti et al, 2018; Vilkomerson et al, 1992), radiology (Kennedy, 2005; Wu and Sherar, 2002), and more. These focusing transducers take on one of two surface profiles: the spherical segment is the shape defined by cutting a sphere with a pair of parallel planes, whereas a spherical cap is the smaller part of a sphere cut by a single plane.…”
Section: Introductionmentioning
confidence: 99%
“…Chest ultrasonography (eg, the evaluation of the entire chest as well as the lungs) furthermore allows exploration of the retrosternal area, a zone often difficult to image with conventional echocardiography and one where postsurgical clots (even compressing the heart) may be detached. 10,11 In summary, CXR continues to hold a great diagnostic utility in cardiac surgery; however, low-radiation dose CT scan (preoperatively) and chest ultrasonography (postoperatively) are valid complementary or alternative examinations (Figure 1). FIGURE 1.…”
mentioning
confidence: 99%